2017
DOI: 10.1038/srep44750
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of Masked Endotoxin

Abstract: Low endotoxin recovery (LER) is a recently discovered phenomenon describing the inability of limulus amebocyte lysate (LAL)-based assays to detect lipopolysaccharide (LPS) because of a “masking effect” caused by chelators or detergents commonly used in buffer formulations for medical products and recombinant proteins. This study investigates the masking capacities of different buffer formulations and whether masked endotoxin is biologically active. We show that both naturally occurring endotoxin as well as con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 19 publications
2
56
0
Order By: Relevance
“…7). Our finding is consistent with previous reports demonstrating that LPS, similar to HVEM-(Fc*), enhanced the expression of activation markers CD40, CD80, and CD83 but not the expression of CD86 (58,61). Recent human and mouse studies have shown that CD80 and CD86 have differential roles in different disease states (62)(63)(64)(65).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…7). Our finding is consistent with previous reports demonstrating that LPS, similar to HVEM-(Fc*), enhanced the expression of activation markers CD40, CD80, and CD83 but not the expression of CD86 (58,61). Recent human and mouse studies have shown that CD80 and CD86 have differential roles in different disease states (62)(63)(64)(65).…”
Section: Discussionsupporting
confidence: 93%
“…7A) and flow-gated monocytes in PBMC cultures ( Fig. 7B), consistent with Schwarz et al (58) who also found upregulation of CD80, CD83, and CD40 but downregulation of CD86 in response to LPS. Similar to HVEM-(Fc*), HVEM-His also activated both monocytes and NK cells in PBMC cultures (Supplemental Fig.…”
Section: Hvem-(fc*) Promotes Activation Of Monocytessupporting
confidence: 89%
“…[214] It has been shown that specific components, including citrate, Triton X-100, and bovine serum albumin hinder reliable LPS recognition by commercially available LPS detection assays. [215] From these data, we can conclude that effects of NM on immune cells must be analyzed very carefully to distinguish potential contaminating LPS effects from real NM-mediated effects. However, due to their ability to interact with endotoxin and due to their optical and physical properties, novel LPS detection platforms involving NM may be developed in the future.…”
Section: Interaction Of Bacterial Molecules With Nanomaterialsmentioning
confidence: 92%
“…Endotoxin content was determined by Limulus amebocyte assay (PYROTELL®-T, Associates of Cape Cod, MA, USA) according to the manufacturer’s instructions. Selected proteins were also tested for masked endotoxin using a NFκB reporter assay based on HEK293 cells overexpressing TLR4, MD-2, and CD14, as previously described 27, 28 .…”
Section: Methodsmentioning
confidence: 99%